TAXING THE NET MARGINS OF COOPERATIVES IN TURKEY (Third Sector Social Economic Review, 2016)
It is very common approach that setting advantageous tax treatment to stimulate the cooperatives because of their contribution to economy, special sectors and groups and to avoid negative consequences of cooperative taxation. In this study, general view and rationales of cooperative taxation procedure and its Turkey practice were examined.There are some conditions which are coherent with principle of cooperatives to take advantage of these benefits.These conditions are highly effective to determine both the tax status of cooperatives and patronage income.
Keywords: Cooperatives; Taxation; Patronage income; taxation of cooperatives; net margins of cooperative